REFLECTIONS ON 21st CENTURY LEADERSHIP: AN INVESTIGATION INTO ACTION INQUIRY AS A DISCIPLINED LEADERSHIP PRACTICE AND ITS EFFECTS ON INDIVIDUAL, TEAM AND ORGANISATIONAL TRANSFORMATION - Jacobs, Oliver K D (2010)
This management project investigates action inquiry as a disciplined leadership practice and its effects on individual, team and organisational transformation. Action inquiry is a practice that aims to help leaders realize different ways of knowing, learning, interacting and arranging their organisations to promote greater effectiveness, integrity, mutuality and sustainability whereby complexities of 21st century operating environments can be more viably met. The present research employs an action research method whereby the researcher triangulates between the accounts of five individuals from a range of organisations who have begun to practice action inquiry and the accounts of four individuals who practice action as part of their consulting practice including Bill Torbert, the key writer, consultant and exponent of action inquiry with the aim of addressing the following problems: (a) the need for a new paradigm of leadership tools and skills for the 21st century in light of current financial, ecological, social and political complexities; (b) the necessity for additional research into action inquiry, which is known only to a small community of practitioners; (c) the difficulty in understanding the complex requirements of action inquiry; and, (d) the challenges of integrating action inquiry in a conventional business world. The research results have the following implications: that action inquiry offers a powerful approach to leadership and can increase a leader’s ability to manage 21st century complexity; that leaders can increase the leadership skills and the performance of their senior management teams through a practice of action inquiry; and, that action inquiry may only be suitable at present in special organisations or situations owing to the radical shift from Western epistemology and ontology implicit in the approach, which makes it difficult for most people to practice on a continual basis.